Tohoku Recovery Challenges, Potentials and Future - Shaw, Rajib (Springer, 2015)
The March 11 disaster in 2011, known as the Great East Japan Earthquake and Tsunami, caused extensive damage in various sectors. Through the recovery process, special lessons are being learned and applied in the affected region. This book attempts to draw lessons from different issues and sectors such as policy perspectives (both national and local), the role of international NGOs, fishing industries and other livelihoods, temporary housing, health, heritage, and lesson sharing. The book outlines the need and approach for sharing the lessons with wider communities in developing those lessons. Based on intensive field research, the book also provides some key lessons from community-based recovery in the affected regions of Iwate, Miyagi, and Fukushima prefectures.